2003
DOI: 10.1046/j.1464-410x.2003.04360.x
|View full text |Cite
|
Sign up to set email alerts
|

Superficial bladder tumours: analysis of prognostic factors and construction of a predictive index

Abstract: predictive index (PI). The algebraic sum of the regression coefficients of the factors with independent and significant association with disease-free survival for each case represented a proportional hazard score (PHS). The PI was validated in another series of 156 patients (validation series) in whom the same regression coefficients for the same significant factors as the test series were used to categorize it into three risk groups. KaplanMeier survival curves were plotted to compare the different risk categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 38 publications
7
52
2
1
Order By: Relevance
“…These results confirm the importance of tumour grade as a stage independent prognostic factor (Ali-El- Dein et al, 2003;Nishiyama et al, 2004) and are consistent with the work of O 'Quigley et al (1981), who reported that an elevated C-reactive protein concentration, measured by radial immunodiffusion and using the limit of sensitivity of 12 mg l À1 as a cutoff, was associated with poor survival in patients with invasive bladder cancer.…”
Section: Discussionsupporting
confidence: 91%
“…These results confirm the importance of tumour grade as a stage independent prognostic factor (Ali-El- Dein et al, 2003;Nishiyama et al, 2004) and are consistent with the work of O 'Quigley et al (1981), who reported that an elevated C-reactive protein concentration, measured by radial immunodiffusion and using the limit of sensitivity of 12 mg l À1 as a cutoff, was associated with poor survival in patients with invasive bladder cancer.…”
Section: Discussionsupporting
confidence: 91%
“…23 If further studies confirm this benefit, routine screening of high-risk populations could possibly lead to diagnosis at a lower stage. 24 Our data show that in a comparison of diagnosis years 1993-1996 and 1997-2000, 5-year survival rates for all stages of bladder, ureteral, and renal pelvis TCC-with the exception of stage I bladder TCC-did not Several studies have shown that higher tumor grade is a risk factor for lower progression-free survival, 25,26 although these studies did not address overall survival. It is possible that the small decrease in 5-year survival for stage I bladder cancer could be because of the increase in the proportion of high grade tumors, although other factors could contribute, as well.…”
Section: Discussionmentioning
confidence: 66%
“…Diversos estudios han identificado esta variable como predictora en la evolución del tumor [26]. Nuestro objetivo es establecer el pronóstico y tratamiento una vez se realiza la RTU y se dispone del estudio anatomo-patológico que siempre es previo a la cistoscopia de los tres meses tras RTU.…”
Section: Discussionunclassified